(untitled) (Kronika Bydgoska, 2020)
Bydgoszcz returned to Poland after ratification of the Treaty of Versailles, on January 20, 1920. Until 1938, it had been part of the Poznań Province and was the biggest county seat in Poland. Since April 1, 1938, it was within the limits of the Pomeranian Province. It had the status of municipality and urban county both under the laws inherited from the invaders (until 1933), and the act “on partial change of the territorial government system” dating from 1932. Its legislative body was the Municipal Council, and the executive authority was the Town Magistrate led by the Mayor. Initially, the Municipal Council consisted of 60 people, and since 1933 - there were 48 of them. In the beginning, the Council served a four-year term, and under the provisions of the new act, since 1933 - a five-year term. The Mayor was theoretically elected for a twelve-year term, but none of the Bydgoszcz Mayors had held his position for such a long time. The first appointed mayor of Bydgoszcz was Jan Maciaszek (in 1920-1921), followed by Wincenty Łukowski (1921-1922), Bernard Śliwiński (1922-1930), and Leon Barciszewski (1932-1939).